ON INVESTIGATING THE SYMBOLIC POWER OF EDUCATIONAL ENTERPRISES IN NTT PROVINCE: A LITERATURE REVIEW - Yulius Nahak; Markus Budiraharjo (Sanata Dharma University, 2022)
From a Bourdieuan perspective, the production of knowledge in the form of empirical studies validates the symbolic power of certain groups. It is arguably proposed that the more empirical studies published in particular groups of people, the more robust the symbolic power of the respective group is. This study is set to reveal the degree of academic productivity of East Nusa Tenggara as a symbolic power owned by scholars in the area, as demonstrated by empirical studies conducted to investigate educational issues in the area. Two research questions were proposed namely: (1) what areas of inquiries did the researchers pursue; and (2) what are their major findings? Sixty-four scholarly articles related to the English learning-teaching (published from 2016 to 2021) were analyzed using document analysis methods to identify the most up-to-date research themes. The results indicated that teaching strategies and material developments are the highest numbers with 41 articles; factors that affect the English language learning were 14 articles; the teaching competencies were 4 articles, and the perception of English learning-teaching were 5 articles. The conclusion is that academic production is low, cross-validating that low symbolic power correlates to more concrete components (i.e., a high degree of poverty).